Guinea : Requests for Disbursement Under the Rapid Credit Facility and For Modification of Performance Criteria Under the Extended Credit Facility Arrangement. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2014)
EXECUTIVE SUMMARY Guinea is suffering from an outbreak of Ebola, which has become a humanitarian crisis with a significant economic impact. Preliminary estimates suggest a negative impact on 2014 growth, which will be markedly lower. Government revenue is showing a substantial shortfall and the response to the Ebola outbreak entails additional critical spending needs. The exchange rate has started to depreciate. The authorities intend to adopt a tighter monetary policy to address the transitory balance of payments shock. Performance under the ECF-supported program has remained satisfactory. Preliminary data indicate that all performance criteria (PCs) under the program for end-June 2014 were met. There has also been further progress with structural reform. The authorities have requested additional IMF financial assistance to meet urgent fiscal and balance of payments needs not anticipated at the time of the recent program review. Such assistance cannot be provided in the form of an augmentation of access under the ECF arrangement at this time since a review associated with the most recent availability date has not yet been completed because of delays in program implementation associated with the 2013 parliamentary elections. The authorities have requested a disbursement under the Rapid Credit Facility (RCF) because the urgent balance of payments need is characterized by a financing gap that, if not addressed, would result in an immediate and severe economic disruption. Moreover, Guinea's balance of payments difficulties are caused primarily by a sudden exogenous shock and not by a withdrawal of financial support by donors, and its balance of payments need is expected to be resolved within one year with no major policy adjustments being necessary. As such polices remain guided by the objectives of the ECF-supported program. Staff supports the authorities' request for a disbursement under the RCF of 25 percent of quota (SDR 26.775 million). It also supports the authorities' request for a modification of the end-September indicative targets and end-December 2014 PCs under the ECF arrangement, including program adjustors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet